Platelet associated immunoglobulins in primary biliary cirrhosis: a cause of thrombocytopenia?. Issue 10 (October 1985) - Bassendine, M F; Collins, J D; Stephenson, J; Saunders, P; James, O F
Abstract : Thrombocytopenia in cirrhotic patients is usually attributed to splenic pooling whereas in idiopathic thrombocytopenic purpura it is related to platelet bound immunoglobulin (PA-IgG). Since primary biliary cirrhosis (PBC) is an autoimmune disorder we have undertaken a prospective study to assess the frequency and possible relationship of PA-IgG to thrombocytopenia in this condition. Sixty-two primary biliary cirrhosis patients (28 precirrhotic; 34 cirrhotic) were studied. Twenty-five patients (40%) had raised PA-IgG of whom 18 had cirrhosis. There was a significant inverse correlation between platelet count and PA-IgG (p less than 0.001) and between platelet count and spleen size (p less than 0.001). Thrombocytopenia (platelets less than 100 X 10(9)/l) was found in nine patients (15%); all nine had raised PA-IgG and eight were cirrhotic with an enlarged spleen. Two cirrhotic patients with persistent thrombocytopenia and bleeding episodes were treated with prednisolone and showed a useful therapeutic response. These results suggest that immune mediated platelet destruction and splenic pooling of platelets may both play a part in the thrombocytopenia observed in primary biliary cirrhosis.